Unboxing the Power of Communication in Empowerment Process - wayan Suadnya (JCommsci - Journal of Media and Communication Science, 2023)
Empowerment is one of the popular concepts in the field of social science and community development. In Indonesia, the word empowerment started to be used in 1998. Recently many empowerment projects were implemented in Indonesia but most of them failed to achieve their goals. The question is, then, what causes empowerment programs to fail? Many factors lead to the program fail, however in this paper, the focus of discussion will be the power of communication in empowerment processes. Empowerment is a process where individuals, groups and communities may obtain control over their lives. The empowerment process is an effort to reduce powerlessness by equipping people with self-awareness, self-competence, self-confidence, self-determination and perceived access to. To accelerate these effort, communication plays important roles. Communication is simply the act of transferring information from one person or group to another. Similar to empowerment: the process to transfer power from one person or organisation to others. Through effective communication people feel more empowered, developed a sense of belonging and responsibility. Most importantly, when the the communication process are open, people feel more comfortable with the relationship developed by change agent. As a result, they have feeling being empowered. The powering process. Consists of two mirror-image that show dialectical processes such as empowering and overpowering (disempowering). The process will undergo empowering when the change agent communicates clearly, honestly, caring, caring, valuing, respecting others and affirming, enhancing, and growing; these will lead to people being free, having self-control and independence and will become overpowering/disempowering if communication is unclear with distortion, objectifying, devaluing, diminishing, negating, constricting and subsuming these will lead to a feeling of being controlled, dominated and make them dependence.